Ascorbic Acid Deficiency (Scurvy) in a Toddler With Restricted Dietary Intake Presenting With "Leg Weakness" and a Rash. (August 2014) - Cain, Meghan; Harris, Malinda; Kim, Kristin; Homme, Jason H.
This report describes a toddler who presented to the emergency department with reported leg weakness and a petechial rash who ultimately was diagnosed with severe ascorbic acid deficiency (scurvy) due to restricted dietary intake. The diagnosis was delayed, and this report highlights the role of a detailed dietary history as part of the diagnostic process.